Suggestions for Addressing Clinical and Non-Clinical Issues in Palliative Care - Cascella, Marco; John Stones, Michael (IntechOpen, 2021)
Data from the World Health Organization indicate that about 40 million people worldwide require palliative care each year. We must face this enormous problem with appropriate welfare policies and training of up-to-date and competent personnel. In this context, a book that collects the experiences of authors with diverse backgrounds, and operating in different settings of palliative care, can be added to the many editorial products on the subject. Over five sections, this volume addresses such topics as palliative care in children, infants, and gynecologic oncology patients; the role of the caregiver; the use of drugs; and ethics, organization, and policy issues. Although this book should not be considered as an exhaustive treatise on palliative care, the many topics covered and the experience and competence of the authors involved make it a useful tool for those who are already experts in the field as well as those who are studying this field.